2008
DOI: 10.1111/j.1744-9987.2008.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Status of Plasmapheresis for the Treatment of Toxic Epidermal Necrolysis in Japan

Abstract: This study describes the efficacy of plasmapheresis for the treatment of toxic epidermal necrolysis (TEN), as reported in Japan. TEN patients treated with plasmapheresis were collected from Japanese literature. The type of plasmapheresis, number of sessions, efficacy of plasmapheresis, and present outcome were examined. Forty-seven TEN patients treated with plasmapheresis have been reported in the literature: 19 men and 28 women with ages ranging from 1 to 96 years (mean 50.3 years). Twenty-five of these treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…Reau et al noted that the cell death receptor CD95 (Fas) and its ligand (Fas-L) have been implicated in bile duct injury. 2 Similarly, elevated levels of Fas-L have been found in TEN patients, 16 and a case series showed resolution of the TEN mucosal damage once plasmapheresis was initiated, correlating with removal of Fas-L from the serum. 17 Its use in patients with isolated VBDS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Reau et al noted that the cell death receptor CD95 (Fas) and its ligand (Fas-L) have been implicated in bile duct injury. 2 Similarly, elevated levels of Fas-L have been found in TEN patients, 16 and a case series showed resolution of the TEN mucosal damage once plasmapheresis was initiated, correlating with removal of Fas-L from the serum. 17 Its use in patients with isolated VBDS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmapheresis is valued for its rapid results, rare side effects, and efficiency in treating patients with TEN refractory to steroids or IVIg. 8 The results of our own experience 11 and the findings in other case reports, 12 case series, 13 and retrospective cohort studies 8 have consistently indicated clinical benefits with plasmapheresis, and additional research on this method has been recommended. 1,7 Regardless of the therapeutic option chosen, a comprehensive team approach that emphasizes supportive care is essential for any patient with TEN.…”
Section: Treatmentmentioning
confidence: 99%
“…Only a few investigators have examined this topic in detail. A large-scale (47 patients) study of plasmapheresis treatment and TEN by Yamada et al 8 revealed that even a low number of cycles (mean, 3.1) had good efficacy (80.9%), and mortality (23.4%) was lower than predicted in patients with the most severe and resistant form of SJS or TEN. A major difficulty limiting further study of this treatment method is the low incidence of TEN, a situation that results in few patients who could potentially be included in prospective studies.…”
Section: Painmentioning
confidence: 99%
See 2 more Smart Citations